A new genus and three new species of Lycoperdaceae (Agaricales) from Southern China revealed by molecular phylogeny and taxonomy - Xin Yang; Songjing Duan; Mei Li; Dongxu Li; Rongcong Yang; Shihui Zhang; Taimin Xu; Wen Li; Hongmin Zhou; Changlin Zhao (MycoKeys)
Lycoperdaceae (Agaricales, Agaricomycetes) is a taxonomically significant fungal family based on the globally distributed and morphologically defined puffball structures. In the present study, one new genus, Lycoperdia, and three new species, viz. Calvatia phlebioides, Lycoperdia tomentosa, and Morganella minima, collected from southern China are proposed based on a combination of morphological characteristics and molecular evidence. Calvatia phlebioides is characterized by broadly obpyriform to turbinate basidiomes and globose to subglobose basidiospores with a short pedicel. Lycoperdia tomentosa is characterized by pyriform basidiomes, tomentose exoperidium, and globose to subglobose basidiospores with a long pedicel. Morganella minima is characterized by tiny basidiomes (5–8 mm in diameter, 3–7 mm in height), globose to subglobose basidiospores with distinct spines, and a short pedicel (<0.5 μm). Sequences of the internal transcribed spacers (ITS), nuclear large subunit ribosomal RNA (nLSU), and RNA polymerase second largest subunit (rpb2) of the nuclear ribosomal DNA (rDNA) markers of the studied samples were generated, and the phylogenetic analyses were performed with maximum likelihood and Bayesian inference methods. The results showed that our collections were clustered within the family Lycoperdaceae. The phylogenetic tree inferred from the ITS+nLSU sequences revealed that all four new taxa were clustered into the family Lycoperdaceae, in which Lycoperdia tomentosa formed a monophyletic lineage. The phylogenetic tree inferred from the ITS+nLSU+rpb2 sequences revealed that one new taxon, Calvatia phlebioides, was clustered into the genus Calvatia, sister to C. longisetulosa. The phylogenetic tree inferred from the ITS+nLSU sequences revealed that Morganella minima was clustered into the genus Morganella, forming a monophyletic lineage. Full morphological descriptions, illustrations, and phylogenetic analysis results for the new genus and three new species are provided.